7th grade revolution - Gardner, Liana (Vesuvian Books, 2017)
Seventh "grade turns out to be anything but normal when teachers announce the students' bloodless revolution succeeded and they are now in charge. After conducting a secret-ballot vote on policy, the 7th graders emerge to find the school evacuated and the FBI lurking outside with the task of unearthing a treasure of national importance"--Amazon.com.